2015
DOI: 10.5304/jafscd.2015.052.019
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Local Procurement in Farm to School Programs: An Exploratory Investigation

Abstract: Farm-to-school (FTS) programs have become more widely adopted in recent years because of their potential to mitigate childhood obesity, as well as their economic development and educational benefits. As a result of FTS programs' diverse purposes and grassroots nature, the types of activities they encompass vary considerably from program to program and no systematic measures of impact have emerged. Furthermore, FTS programs launched in colder climate regions may be particularly challenging due to a shorter grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Part of the rationale for these investments is due to a major perceived barrier for increasing sales to schools: complex supply chain networks required for school delivery (Vogt and Kaiser, 2008; Roche et al , 2015; Matts et al , 2016; Becot et al , 2017). Previous research found that farm sales to schools and institutions are limited due to challenges with supply chain logistics and regulations (Ohmart, 2002; Izumi et al , 2010; Dimitri et al , 2012; Thompson et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Part of the rationale for these investments is due to a major perceived barrier for increasing sales to schools: complex supply chain networks required for school delivery (Vogt and Kaiser, 2008; Roche et al , 2015; Matts et al , 2016; Becot et al , 2017). Previous research found that farm sales to schools and institutions are limited due to challenges with supply chain logistics and regulations (Ohmart, 2002; Izumi et al , 2010; Dimitri et al , 2012; Thompson et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Per the 2015 National Food Hub Survey, 31% of food hubs have K-12 foodservice customers (Hardy et al , 2016). In their study of FTS in Vermont, Roche et al , (2014) find that food hubs can play an integral role in overcoming many of the barriers associated with direct FTS sales, including consistent availability, facilitating communication, food safety assurance and issues of quality control. Fischer et al (2015) similarly note that the commitment to supporting the economic viability of farmers is one of the key attributes that make food hubs distinct from traditional food distribution business.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schools operate on limited budgets, and so maintaining low costs is extremely important to ensure cafeterias continue to operate and serve children. Some studies have suggested that, in addition to strategies to reduce the cost of local food, the creation of programming that builds relationships between school foodservice buyers has the potential to result in increased local procurement (Roche, Conner, & Kolodinsky, 2015). The National Farm to School Network, for example, has a number of tools, including its State Farm to School Networks Toolkit that includes information for establishing a robust network structure (National Farm to School Network, 2018).…”
mentioning
confidence: 99%
“…Food hubs, which the USDA defines as "a centrally located facility with a business management structure facilitating the aggregation, storage, processing, distribution, and/or marketing of locally/regionally produced food products," can promote local food procurement by reducing the burden on schools that would otherwise need to source from multiple producers. While case studies suggest that food hubs can support farm to school programs (Roche, Conner, and Kolodinsky 2015), this potential relationship warrants further study (Schafft, Hinrichs, and Bloom 2010). Farm to school policies, which can include grant programs or increased funding for school meals, serve to mitigate the increased costs of local food procurement.…”
Section: Introductionmentioning
confidence: 99%